Determinants of Employee Organizational Citizenship Behaviour: Evidence from Village-Owned Enterprise Organisations in Indonesia - Ahmad, Ahmad (Jurnal Ekonomi, 2024)
Organizational citizenship behaviour is voluntary behaviour that exceeds the basic needs of workers, which is beneficial to the organisation and is not related to the compensation system. This study aims to determine the factors of OCB behaviour in Village-Owned Enterprises or known as BUMDes based on cases in Indonesia. This study used 129 samples collected by convenience sampling technique. Primary data was collected using a direct survey of permanent employees. OCB measurement consists of 20 indicators. Based on factor analysis, nine organizational citizenship behaviour factors were formed. The first factor is altruism, followed by sportsmanship, organizational compliance, organizational loyalty, civic virtue, conscientiousness, self-development, good intentions, and finally understanding the situation.